The kinematic model of the basket to handstand on the parallel bars - Velickovic, S.; Kolar, S.; Kugovnik, O.; Petkovic, FD.; Petkovic, E.; Bubanj, S.; Bubanj, R.; Stankovic, R. (Facta Universitatis: Series Physical Education and Sport, 2011)
A model of a successful routine for competitors in artistic gymnastics consists of the most complex coordination elements and their successful execution. One of the most difficult elements on the parallel bars is a ''basket to handstand" The aim of the research was to carry out a kinematic analysis of the element basket to handstand on the parallel bars, in order to ascertain the conditions for the successful construction of the teaching process, which would help in perfecting the element. Mitja Petkovšek, a member of the Slovenian national team and one of the most successful competitors on the parallel bars in the last two Olympic cycles, successfully performed a basket to handstand. Kinematic parameters were determined by using a APAS 3-D video system for the kinematic analysis and which included 17 reference points and 15 body segments. The results of the research defined the kinematic exercise model, which requires four phases 1) upswing from a handstand 2) downswing to upswing; 3) forward swing to upswing; 4) downswing to handstand. A kinematic model, defined in this way, will as a result of its highly informative value undoubtedly facilitate the process of technical preparation for the analysed element. It will also facilitate the process of creating a methodological training procedure, which should first be aimed at the acquisition of each individual phase (the analytical method), and afterwards should concentrate on the successive merging of all the phases, with a multiple execution of the entire element (the synthetic method).